1995
DOI: 10.1128/jb.177.17.5048-5055.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and characterization of the gene encoding the smallest subunit of the three-component membrane-bound alcohol dehydrogenase from Acetobacter pasteurianus

Abstract: The membrane-bound alcohol dehydrogenase (ADH) of Acetobacter pasteurianus NCI1452 consists of three different subunits, a 78-kDa dehydrogenase subunit, a 48-kDa cytochrome c subunit, and a 20-kDa subunit of unknown function. For elucidation of the function of the smallest subunit, this gene was cloned from this strain by the oligonucleotide-probing method, and its nucleotide sequence was determined. Comparison of the deduced amino acid sequence and the NH 2 -terminal sequence determined for the purified prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 24 publications
2
47
0
2
Order By: Relevance
“…21) SldS showed similarity to the small subunits of GADH and 2KGDH, of which the function is also unknown. Kondo et al have suggested that the 20 kDa small subunit of ADH from Acetobacter pasteurianus has a role in the stability of the dehydrogenase subunit and functions as a molecular coupler to the cytochrome c subunit on the cytoplasmic membrane, 30) but the small subunit has no similarity to SldS in amino acid sequence. Although the small subunit of ALDH from acetic acid bacteria contains iron-sulfur clusters, 31) the amino acid sequence of SldS does not have such a binding motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21) SldS showed similarity to the small subunits of GADH and 2KGDH, of which the function is also unknown. Kondo et al have suggested that the 20 kDa small subunit of ADH from Acetobacter pasteurianus has a role in the stability of the dehydrogenase subunit and functions as a molecular coupler to the cytochrome c subunit on the cytoplasmic membrane, 30) but the small subunit has no similarity to SldS in amino acid sequence. Although the small subunit of ALDH from acetic acid bacteria contains iron-sulfur clusters, 31) the amino acid sequence of SldS does not have such a binding motif.…”
Section: Discussionmentioning
confidence: 99%
“…Competent cells of Gluconobacter strains were obtained by the following method: A preculture (1 ml) was transferred into 100 ml of 1% D-sorbitol medium in a 500 ml Erlenmeyer flask with shaking at 30 C for 12 h. Cells were chilled on ice for 30 min before harvesting by centrifugation at 4,000 rpm for 10 min at 4 C, and washed twice with ice-cold 10% (w/v) glycerol. The final cell pellet was resuspended with 0.5-1 ml of ice-cold 10% (w/v) glycerol.…”
Section: )mentioning
confidence: 99%
“…The main source of genetic instability has been attributed to mobile genetic elements, mainly transposons, widely distributed in the genome. Insertion sequences (IS) responsible for EtOH oxidation deficiency, like those of the family IS 12528, were found in the chromosome of A. pasteurianus NCIB 7214 (5 copies) [26], A. aceti 1023 (1 copy) and G. oxydans IFO 12528 (10 copies). Likewise 100 copies of IS 1380 occur in A. aceti 1023 and 74 copies in A. pasteurianus NBRC 3283 [1,27].…”
Section: General Phenotypic Characteristics and Taxonomicmentioning
confidence: 99%
“…The subunit II which molecular size range from 44 to 45 kDa contains three heme c moieties and it is encoded in the adhB gene. The third and smallest subunit (20 kDa), encoded in the adhS, helps the two functional subunits with their association to the membrane protecting the catalytic subunit from proteolysis and it contributes to the correct conformation of the ADH complex for electron transport on the periplasmic surface [26,45]. Oxidation of EtOH occurs at PQQ site that acts as two-electron redox mediator; electrons are initially transferred to UQ, which will be re-oxidized by a membrane-associated oxidase.…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…and 5?-GCCTCTAG-AGCAGCCTCAGGGGTGATCCGC-3?) designed from the reported sequence, 20) and cloned into the Pst I-XbaI site in pHSG298 (Takara Shuzo, Japan). Then, the ampR gene of pUC18 (Takara Shuzo, Japan) was ampliˆed with the primers 5?-TTC-AGATCTCATTCAAATATGTATCCGCTC-3?…”
Section: Methodsmentioning
confidence: 99%